Fatores associados à adesão ao tratamento de pacientes com diabetes mellitus - Faria, Heloisa Turcatto Gimenes (2013)
Objective: Investigating the association between adherence to treatment of type 2 diabetes mellitus and socio-demographic, clinical and metabolic control variables. Methods: Cross-sectional study with 423 patients with diabetes mellitus. The Fisher’s exact test and logistic regression models were used to investigate the association between adherence to treatment and the studied variables. Results: There was no association between adherence to treatment of T2DM and socio-demographic and clinical variables. It was found that total cholesterol and HbA1c were significantly associated with adherence to diet (p = 0,036) and exercise (p = 0,006). Conclusion: The chance of a patient with cholesterol within the recommended level adhering to diet is almost five times the chance of the patient in poor lipid control. The chance of patients with poor glycemic control adhering to exercise is almost twice the chance of those who keep adequate glycemic control.